A Structural Model of Green Purchase Behavior: Mediating Effects of Green Perceived Value and Green Trust and the Moderating Effect of Environmental Knowledge - Siahaan, Febri; Rismanto, Caesar; Priscillia, Amanda Sona (Universitas Brawijaya, Indonesia, 2026)
The growing urgency to reduce plastic waste and promote sustainable consumption has increased the relevance of eco-bags, particularly among Generation Z consumers who are increasingly aware of environmental issues and responsive to green lifestyle trends. This study aims to examine the factors influencing Generation Z’s green purchase behavior toward eco-bags by analyzing the effects of green product attributes, subjective norms, and green brand image, with the mediating roles of green perceived value and green trust and the moderating role of environmental knowledge. Using a quantitative explanatory approach, data were collected through an online survey of 300 Generation Z consumers aged 18-27 in Tangerang Raya, Indonesia, using purposive sampling. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that green product attributes, subjective norms, and green brand image significantly influence green perceived value, which subsequently strengthens green trust and encourages green purchase behavior. Environmental knowledge demonstrates a moderating role in several relationships, indicating that consumers with higher environmental awareness interpret sustainability cues more critically. These findings highlight the importance of credible green product attributes, authentic green branding, and social influence in encouraging sustainable purchasing behavior among younger consumers.